Pengaruh Kapabilitas, Peluang, dan Motivasi Terhadap Perilaku Tenaga Kesehatan dalam Melakukan Perawatan: Tinjauan Systematic Literatur Review - Harto, Dwi; Ernawati, Ernawati; Aisah, Siti (Universitas Malahayati, 2025)
ABSTRACT Quality healthcare is a fundamental right of every individual. The quality of care provided by healthcare professionals depends heavily on various factors, one of which is their behavior. Healthcare professionals' behavior in providing care is influenced by various factors, which can be grouped into capabilities, opportunities, and motivation. This article aims to examine how capabilities, opportunities, and motivation influence healthcare professionals' behavior in providing care through a systematic literature review. This study used a systematic review of literature discussing the influence of capabilities, opportunities, and motivation on healthcare professionals' behavior in providing care using the PRISMA method. Searches were conducted in PubMed, Scopus, Web of Science, Cochrane Library, and Google Scholar using the keywords